Analisis Penyusunan Rencana Kerja Pada Satuan Kerja Perangkat Daereah ( SKPD ) BPPRD-SU - Widya Rizky Amelia; Muhammad Ikhsan Harahap (Universitas Muhammadiyah Enrekang, 2022)
The work plan is referred to as a process that has the potential to achieve the results to be achieved over the next one year while taking into account the potential, opportunities and constraints that may or may arise, the work plan includes the vision, mission, strategy, goals and objectives of an organization, and also about the main tasks and functions of the organization, as well as programs and activities that include work plans that will be carried out within one year, the preparation of a work plan is the implementation of a planning concept that plays a role in the organizational managerial process as a determining factor for the success of achieving goals and objectives as well as achieving the vision and mission of an organization. organization. Preparation of the Work Plan at the Regional Tax and Levy Management Agency of North Sumatra Province, compiled from the Minister of Home Affairs No. 86 of 2017 concerning the method of Programming, Regulation, and Regional Development Assessment, procedures for Assessing the Concept of Regional regulations regarding the concept of long-term development, the concept of development regional middle time and the concept of regional ruler activities. The concept of this activity is based on the estimation and progress of the strategic environment, both internal and external, which greatly influences the implementation and management of regional levies. The work plan includes the vision, mission, goals, policies, programs and activities to be carried out within one year. Based on the identification and pressing problems and with reference to the income of capabilities in the achievement of strategic plan performance and synergy with national policies, so that the objectives and targets for the acquisition of the Regional Tax and Levy Management Agency of North Sumatra Province in the Regional Apparatus Work Unit (SKPD) must create target capability of the proposed activity in its budget. The delegation of power is not only the right to use the budget, but also has implications for the role. Associated with financial data, SKPD must always recognize how many public budgets have been entered.